Equitable Distribution of Community Welfare: Alignment of Local Government Capacity and Territorial Challenges - Said, Moh (FIA UB, 2019)
This paper examines the dynamics of the implementation of decentralization in the archipelago of Sumenep Regency, related to the distribution of development and equitable distribution of community welfare. The effectiveness of regional government administration leads to the realization of community welfare. However, each autonomous region faces the challenges of different territorial conditions. Geographic conditions characterized by archipelago are a big challenge for regional governments. Difficult accessibility causes limited mobility of people and goods which results in difficulties in the implementation of public services. It is found that equitable distribution of community welfare must be encouraged through accelerating development in the archipelago. Then, there must also be an increase in the capacity of the regional government so that the implementation of development in the archipelago area can be carried out well, which in turn, welfare distribution can be realized.